2012
DOI: 10.1038/ejcn.2012.48
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different fractions of whey protein on postprandial lipid and hormone responses in type 2 diabetes

Abstract: BACKGROUND/OBJECTIVES: Exacerbated postprandial lipid responses are associated with an increased cardiovascular risk. Dietary proteins influence postprandial lipemia differently, and whey protein has a preferential lipid-lowering effect. We compared the effects of different whey protein fractions on postprandial lipid and hormone responses added to a high-fat meal in type 2 diabetic subjects. SUBJECTS/METHODS: A total of 12 type 2 diabetic subjects ingested four isocaloric test meals in randomized order. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 39 publications
(42 reference statements)
2
42
0
Order By: Relevance
“…Milk proteins have been extensively investigated for their insulinotropic and glucose-lowering effects in healthy subjects (73,75,82,83,(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) and to a limited extent in individuals with suboptimal glucose control (100)(101)(102)(103)(104)(105)(106) . The dose varied significantly between studies from as little as 10 g (92,105,106) -51 g (91) .…”
Section: Short-term Studies On Glycaemic Controlmentioning
confidence: 99%
“…Milk proteins have been extensively investigated for their insulinotropic and glucose-lowering effects in healthy subjects (73,75,82,83,(90)(91)(92)(93)(94)(95)(96)(97)(98)(99) and to a limited extent in individuals with suboptimal glucose control (100)(101)(102)(103)(104)(105)(106) . The dose varied significantly between studies from as little as 10 g (92,105,106) -51 g (91) .…”
Section: Short-term Studies On Glycaemic Controlmentioning
confidence: 99%
“…In general, fat is a major determinant of the postprandial responses of gut peptides. Accordingly, studies have shown that both carbohydrate and fat content are of importance for the postprandial response of GLP-1 and GIP in healthy subjects and in patients with diabetes type 2 [19,20,21]. The effects of type 1 diabetes on incretin secretion or its effects after a fat-rich meal have been less well studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of gastrointestinal dysmotility or autonomic neuropathy on incretin or leptin secretion has not been fully elucidated in diabetes [6,7,15,20,21], although these hormones have been shown to affect gastrointestinal motility, and are influenced by idiopathic gastroparesis [8,11,16].…”
Section: Introductionmentioning
confidence: 99%
“…Whey protein fractions (whey isolate and whey hydrolysate) added to a fat-rich meal lowered postprandial triglyceride responses in type 2 diabetic subjects. Both components provoked a higher insulin response (Mortensen et al 2012). A hydrolyzed whey protein-based supplement was fed to rats for 30 days.…”
Section: Anti-diabeticmentioning
confidence: 99%